PENGARUH MOTIVASI KERJA, KOMPENSASI, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI JAWA POS RADAR KEDIRI - Maulida Fitria; Taufik Akbar; Ahmad Idris (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the influence of work motivation, compensation, and job satisfaction on employee performance at Jawa Pos Radar Kediri. The research was designed using a quantitative descriptive approach to measure the relationships between independent and dependent variables through statistical analysis. Data were collected from all 47 employees using a structured questionnaire based on a Likert four-point scale, supported by observation and documentation to ensure data validity. The collected data were analyzed using multiple linear regression through IBM SPSS 26, including classical assumption tests to verify reliability and normality. The findings indicate that work motivation, compensation, and job satisfaction simultaneously have a positive effect on employee performance. However, compensation has the most dominant influence, suggesting that fair and transparent remuneration significantly improves employees’ responsibility and productivity. Meanwhile, work motivation and job satisfaction show positive but partial and nonsignificant effects, implying that psychological and environmental factors still need to be strengthened to optimize performance outcomes. The novelty of this research lies in its empirical validation of human resource factors within the media industry, emphasizing that balanced motivational and reward systems can enhance both individual and organizational performance. These findings contribute to the field of human resource management and serve as a valuable reference for future research in organizational behavior and workplace productivity improvement.